Study of gut content and toxin properties of coral crabs from satang Island of Sarawak - Nanthinidevi, A/P Bathumalai (Universiti Malaysia Sarawak (UNIMAS), 2012)
The study of toxin properties was carried out on four species of coral crab, Eriphia smilhii, Eriphia sebana, Ozius gullalus and Alergalis inlegerrimlls from Satang Besar Island, Sarawak. A total number of 52 coral crab specimens were collected by hand during low tide in night on September'll sampling and 34 coral crab specimens in March' 12 sampling. The coral crab specimens were identified and physical measurements of the crab's carapace width, carapace length and body weight were measured and recorded. The gut content analysis was carried out on the 34 specimens collected during second sampling. All the gut contained bivalve shell, coral fraction, algae, sand particles, gastropod fraction, crustacean, copepod and debris. No define conclusion were made based on whether the presence of toxin is endogenous or exogenous in the crab. In thin layer chromatography (TLC) analysis using I-butanol-acetic acid-water (2: I: I) solvent system, the four species of coral crab appendages, whole body tissue, claw, internal organ and egg showed Rr value that varies with range 0.15 to 0.40 and only O. gullalus appendages and A. inlegerrimlls internal organ showed similar result to tetrodotoxin (TTX) standard ( Rc =0.20). Further analysis using liquid chromatography-tandem mass spectrometry (LC-MSfMS) was conducted to verify and determine the amount of TTX. Based on the analysis, the four coral crab species were non-toxic with the range of 0.24 MU/g to 0.29 MU/g. No presence of TTX was detected in female E. sebana egg and in female E. smilhii whole body tissues.